1999
DOI: 10.1046/j.1365-2796.1999.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of methylmalonic acid and homocysteine in elderly people. A population‐based intervention study

Abstract: Abstract. Bjo Èrkegren K, Sva Èrdsudd K (University Hospital Uppsala; Skutska Èr Primary Health Care Center, Skurska Èr, Sweden). Elevated serum levels of methylmalonic acid and homocysteine in elderly people. A population-based intervention study. J Intern Med; 246: 317±324.Objectives. There is uncertainty amongst clinicians about the definitions of cobalamin and folate deficiency and therefore about the indications for treatment. In this report we present the results of systematic cobalamin and folic acid tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…This suggests that some of the respondents with low serum vitamin B 12 may have macrocytosis. Bjorkegren & Svardsudd (1999), reported that, although MMA increases with age, it is not necessarily correlated with any abnormality of the classical haematological indices. Excessive reliance on the evidence of haematological indices may not be an efficient way of detecting incipient vitamin B 12 deficiency in older people, and better ways of monitoring functional vitamin B 12 deficiency in populations are clearly needed (Savage et al, 1994;Nilsson-Ehle, 1998).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This suggests that some of the respondents with low serum vitamin B 12 may have macrocytosis. Bjorkegren & Svardsudd (1999), reported that, although MMA increases with age, it is not necessarily correlated with any abnormality of the classical haematological indices. Excessive reliance on the evidence of haematological indices may not be an efficient way of detecting incipient vitamin B 12 deficiency in older people, and better ways of monitoring functional vitamin B 12 deficiency in populations are clearly needed (Savage et al, 1994;Nilsson-Ehle, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Following the early studies that demonstrated the basic relationship between vitamin B 12 and MMA in man (Gompertz et al, 1967;Chanarin et al, 1973;Norman et al, 1982;Carmel, 2000), and which established reliable assay techniques for MMA (Stabler et al, 1986), were a number of key studies showing a surprisingly high prevalence of raised MMA levels in the plasma of older people, where it appeared to provide a more reliable indicator of functional vitamin B 12 status than serum or plasma vitamin B 12 concentrations per se (Lindenbaum et al, 1988;Rasmussen et al, 1989;Moelby et al, 1990;Joosten et al, 1993;Allen & Casterline, 1994;Lindenbaum et al, 1994;Koehler et al, 1996;Baik & Russell, 1999;Bjorkegren & Svardsudd, 1999;Herrmann et al, 2000). Clearly, the ageing process in itself, and the increasing prevalence of age-related medical conditions that impair vitamin B 12 absorption, both increase the probability that people will become vitamin B 12 -deficient as they grow older.…”
Section: Introductionmentioning
confidence: 99%
“…1,8,[10][11][12] However, patients in these studies were preselected for the presence of low serum Cbl levels, and survey studies of ambulatory populations have found elevated MMA levels in many subjects with serum Cbl levels well within the normal range. 16,23,24,[35][36][37][38] Only one study contrasted the serum metabolite levels in 86 patients with clinical responses to Cbl therapy with those in 59 patients who did not improve with Cbl therapy. 9 While 94% of responders had increases of one or both metabolites at least 3 SD above the normal mean, it was also notable that 12 of 61 patients (21%) with normal or less striking increases in MMA were responders, as were 13 of 51 patients (25%) with normal or less striking increases in HCys.…”
Section: Discussionmentioning
confidence: 99%
“…Normal Cbl values were 200 to 1100 pg/mL, but higher reference ranges have been suggested, 11,13,16,17,20,23,24 and the statement "patients with values less than 300 pg/mL may experience unexplained neuropsychiatric or hematologic abnormalities due to occult B12 deficiency" was appended to test reports during the last 4 years of the study. Thus, Cbl levels were defined as low (below 201 pg/mL), intermediate (201 to 300 pg/mL), or normal (above 300 pg/mL).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Homocysteinemia may be caused by several nutritional deficiencies other than B12, including vitamin B6 and folate deficiencies [14]. Depending on the cutoff levels, previous studies have reported the prevalence of vitamin B12 deficiency to be between 10 to 43 % [15][16][17][18]. When serum level < 200 pg/mL was used as cut off, 10 -15 % of old people had vitamin B12 deficiency [21].…”
Section: Introductionmentioning
confidence: 99%